Global, regional, and national burden of ischemic heart disease attributed to non-optimal temperature, 1990–2021: an age-period-cohort analysis of the global burden of disease study - Xia, Xiaoqing; Suona, Deji; Yu, Jing; Zhi, Hong; Wang, Lina (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIn recent years, non-optimal temperature has significantly impacted global health including ischemic heart disease (IHD).MethodsData regarding the burden of IHD caused by non-optimal temperature were sourced from the Global Burden of Disease Study 2021. Temporal trends of the age-standardized mortality rate (ASMR) and the age-standardized disability-adjusted life years rate (ASDR) were estimated by annual percentage change (EAPC) from 1990 to 2021. Age-period-cohort modeling was employed to investigate IHD-related mortality.ResultsThe number of IHD deaths and DALYs resulting from non-optimal temperature experienced a rise of 71.6% and 60.6%, respectively. And it showed regional imbalances: in the region with low-middle socio-demographic index (SDI), it was increased [EAPC for ASMR: 0.39% (95% CI: 0.2%, 0.58%), EAPC for ASDR: 0.33% (95% CI: 0.15%, 0.52%)], while decreased in the high SDI region, [EAPC for ASMR: −3.44% (95%CI: −3.58%, −3.3%), EAPC for ASDR: −3.18% (95%CI: −3.32%, −3.03%)]. APC modeling showed that the global risk of death from IHD caused by non-optimal temperature was increased with age and was generally higher in males than in females. The period effect revealed a higher mortality risk in low-middle and low SDI regions, whereas the birth cohort effect indicated a lower mortality risk in high-middle and high SDI regions.ConclusionsThe IHD burden caused by non-optimal temperature significantly varied according to the genders, SDI regions, and countries from 1990 to 2021. It is crucial to implement effective strategies to mitigate the impact of non-optimal temperature on IHD, particularly among men, the elderly, and the lower SDI regions.